Association of census tract-level incarceration rate and life expectancy in New York State. Issue 10 (27th April 2021) - Holaday, Louisa W; Howell, Benjamin; Thompson, Keitra; Cramer, Laura; Wang, Emily Ai-hua
Abstract : Background: Jail incarceration rates are positively associated with mortality at the county level. However, incarceration rates vary within counties, limiting the generalisability of this finding to neighbourhoods, where incarceration may have the greatest effects. Methods: We performed a cross-sectional analysis of census tract-level state imprisonment rates in New York State (2010) and life expectancy data from the US Small-area Life Expectancy Estimates Project (2010–2015). We modelled fixed-effects for counties and controlled for tract-level poverty, racial makeup, education, and population density from the American Community Survey (2010–2014), and violent crime data from the New York City Police Department (2010). We also examined interactions between incarceration rate and poverty, racial makeup, and population density on life expectancy. Results: Life expectancy at the highest quintile of incarceration was 5.5 years lower than in the lowest quintile, and over 2 years lower in a fully-adjusted model. Census tract-level poverty and racial makeup both moderated the association between incarceration and life expectancy. Conclusion: Census tract-level incarceration is associated with lower life expectancy. Decarceration, including alternatives to incarceration, and release of those currently incarcerated, may help to improve life expectancy at the neighbourhood level.